DIAGNOSTICS OF UNFIRED EARTH WITH METHYLENE BLUE TEST - Tereza Plaček Otcovská; Barbora Mužíková; Pavel Padevět (Acta Polytechnica CTU Proceedings, 2020)
Unfired earth is important historic building material. Final properties of unfired earth constructions are influenced by amount and kind of clay in earth mixtures. Methylene blue test is a method that helps determining the type and amount of clay in earth mixtures. This paper describes research focused on using methylene blue test for analysis of methylene blue dye absorption by montmorillonite clay. The first part of the paper describes principle of methylene blue test and course of experimental measurement. The second part deals with analysis of obtained results. On the basis of experimental measurement it can be stated that methylene blue test is influenced by the stirring time of earth samples with methylene blue solution and dependence between amount of methylene blue dye absorption and amount of montmorillonite clay in earth samples is linear.